2009
DOI: 10.1021/jp9006747
|View full text |Cite
|
Sign up to set email alerts
|

Single- and Multicomponent Vapor-Phase Adsorption of Xylene Isomers and Ethylbenzene in a Microporous Metal−Organic Framework

Abstract: Vapor-phase adsorption of the C8 alkylaromatic components p-xylene (p-x), m-xylene (m-x), o-xylene (o-x), and ethylbenzene (eb) on the three-dimensional microporous metal−organic framework (MOF) Zn(BDC)(Dabco)0.5 (BDC = 1,4-benzenedicarboxylate, Dabco = 1,4-diazabicyclo[2.2.2]octane) was investigated. Single- and multicomponent fixed-bed experiments were carried out at temperatures ranging from 125 to 175 °C and total hydrocarbon pressures up to 0.10 bar. At high pressure, the adsorption capacity for all the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 47 publications
2
58
0
Order By: Relevance
“…(6). Together with the operating conditions, the numerical values of the amount adsorbed for each equimolar quaternary breakthrough can also be found in the literature [37]. Fig.…”
Section: Multicomponent Adsorption Isothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…(6). Together with the operating conditions, the numerical values of the amount adsorbed for each equimolar quaternary breakthrough can also be found in the literature [37]. Fig.…”
Section: Multicomponent Adsorption Isothermsmentioning
confidence: 99%
“…Recently, Nicolau et al [37] have shown that the separation of o-x from the other C 8 components in Zn(1,4-BDC)(Dabco) 0.5 MOF, denoted as MOF 1, is quite efficient. ''BDC'' denotes 1,4-benzenedicarboxylate and ''Dabco'' denotes 1,4-diazabicyclo[2.2.2]-octane.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical support from molecular simulation data will be useful to clarify the a Data taken from [25]. b Data taken from [24]. adsorption phenomena in MOF UiO-66, as well as, to explain the curious maxima in the equilibrium selectivity shown in Fig.…”
Section: Adsorption Of Quaternary Mixtures Of Hexane Isomersmentioning
confidence: 99%
“…In general, dimensions of ortho ‐substituted isomers are larger than those of meta ‐ and para‐ substituted isomers for these substituted aromatics, e.g. EB ≅ para ‐xylene (0.67 nm) < meta ‐xylene (0.71 nm) < ortho ‐xylene (0.74 nm) . The column exhibited high selectivity for the ortho ‐substituted isomers.…”
Section: Resultsmentioning
confidence: 98%